Moderasi Beragama: Konsep dan Implementasi di Perguruan Tinggi Keagamaan Islam Negeri - Baba, Mastang Ambo; Zainal, Nur Fitriani; Subeitan, Syahrul Mubarak (Al-Ulum, 2023)
This research aims to analyze the concept and implementation of religious moderation at two State Islamic Religious Universities (PTKIN), namely IAIN Manado and IAIN Sultan Amai Gorontalo. In qualitative research with a sociological approach, the research results show that the two PTKINs have succeeded in implementing the concept of religious moderation by prioritizing moderate attitudes, tolerance, and dialogue between religious believers in the campus environment. However, challenges such as skepticism and negative perceptions of religious moderation remain obstacles. The role of lecturers and education staff has a significant impact in supporting the implementation of religious moderation. Training programs and special initiatives have proven effective in increasing understanding and awareness of religious moderation among the academic community.